PENGARUH KEPEMIMPINAN MOTIVASI KERJA DAN KOMPENSASI TERHADAP KINERJA PARAMEDIS RUMAH SAKIT IBU DAN ANAK ERIA BUNDA PEKANBARU - Khairunnisa, Mardhatillah Indah; Dewita, Ningsih Suryati; Jushermi, Jushermi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of leadership, motivation and compensation on paramedic performance of mother and children eria bunda pekanbaru hospital. The sampling technique is a method that has been selected census to 104 paramedic who were sampled. The research variables used are leadership (X1) motivation (X2) and compensation (X3) as independent variables and paramedic performance (Y) as dependent variables. The data analysis method used is multiple regression analysis using SPSS 23 for windows. The result showed that: 1) There is a positive and significant effect of leadership on the paramedic performance. 2) There is a positive and significant effect of motivation on the paramedic performance. 3) There is a positive and significant effect of compensation on the paramedic performance. 4) There is a possitive and significant effect of leadership, motivation and compensation on the paramedic performance.Keyword: Leadership, Motivation, Compensation, Peformance